Studio Ghibli : the complete works - Joseph, Daniel (Translator); Otake, Shizuka (Kodansha USA Publishing, LLC, 2022)
"A beautiful, full-color dive into the history and future of Studio Ghibli, Japan's preeminent animation house. In-depth looks at every one of their 26 feature films - including the latest, Earwig and the Witch - means there's something for everyone, while exclusive interviews and rare director's commentary plus behind-the-scenes tidbits will excite even the most devoted Ghibli afficionados. A gorgeous, stirring must-have for Studio Ghibli fans and newcomers alike! From classics like Nausicaa of the Valley of the Wind to the latest work, Earwig and the Witch, this beautiful art book introduces all 26 acclaimed Studio Ghibli films. Take a deep look into Ghibli's first 3D feature film, Earwig and the Witch, with an exclusive interview with director Goro Miyazaki."--